A Case Study Based on CLT through the Task of Ordering Cards Helping the Beginner-Level Learners to Discuss Both Cohesion and Coherence - HIGUCHI, Shoko (Eibeibunka: Studies in English Language, Literature and Culture, 2024)
It is quite difficult for beginner-level English learners to write in paragraphs. They need various skills besides English grammatical skills. For example, it is essential to consider the twin concepts of cohesion and coherence when thinking about paragraph structure. Therefore, it is effective to introduce reading activities to the class of targeting paragraph-level writing.For this research, a class was entrusted with the task of “ordering cards,” which focuses on cohesion and coherence. Twenty-four Japanese university students took a lecture of six connective words (because, when, before, after, but, and) ,and started the task of ordering cards. A sentence from a short story was written on each card, and the students had to order the cards to recreate the original story while cooperating in their team.The researcher recorded the discussion between students and teacher and analyzed the conversation. As a result, this research revealed that students tend to focus on coherence rather than cohesion when they ordered the cards. However, the teacher’s advice was effective in helping them use connective words to order the cards. The effective advice was categorized into three groups; advice that (1) gives new knowledge, (2) suggests reorganizing the main points, and (3) gives part of the correct answers.